Analysis of Social Media Addiction and Usage Purposes Among Secondary-School Students in Turkey - ALTAYEF, Hamid Altayef Abed; KARACI, Abdulkadir (AJIT - E Academic Journal of Information Technology, 2019)
The excessive use of social media has become a social habit in today’s world, and social media addiction affects people worldwide. The purpose of this study is to explore social media use and addiction among secondary-school students, according to several personal variables as reported in a personal information form and a survey form asking respondents to disclose their reasons for using social media and to rate their level of social media addiction. Our research sample consisted of 1005 students studying at public schools in Kastamonu city centre, Turkey. The findings from this study indicated that students have an overall tendency to become social media addicts. Students sometimes use social media to prepare for their courses and in interpersonal interactions. The level of social media addiction is higher among males than females. Males use social media more than females for interpersonal communication. Social media addiction increases as the age of the students increases, and older students use social media more than their younger counterparts to communicate and interact with other people. As internet use increases among students, their use of social media for course preparation and interpersonal interactions increases as do their addictions to social media. The degree of addiction increases as the grade level increases, and the use of social media for course preparation decreases with this addiction. The use of social media at home and in transportation systems has more influence on the formation of social media addiction. Students usually use Facebook, Facebook Messenger and YouTube. They mostly use Facebook to communicate with their friends rather than to prepare for their courses. Thus, Facebook contributes little to their academic improvement. Social media addiction among students using Facebook, Facebook Messenger, YouTube, Twitter and Skype is higher. Most students start to use social media in primary school in the third and fourth grades. Thus, their addiction to social media and the use of social media in interpersonal interactions increase.&nbsp
Keywords: purposes of social media use; sosyal medya kullanım amaçları; social media; Communication. Mass media; QA75.5-76.95; P87-96; Electronic computers. Computer science; sosyal medya; T1-995; ortaokul öğrencileri; facebook; sosyal medya bağımlılığı; Technology (General); social media addiction; secondary-school students; 4. Education